Heterostructured Li4Ti5O12/TiO2/carbon microspheres self-assembled by nanowires as high performance anodes for lithium ion batteries. (10th January 2020) - Zhao, Lili; Song, Ge; Li, Honglei; Yang, Puheng; Xia, Jun; Li, Jiajie; Zhang, Shichao; Xing, Yalan; Zhao, Guangjin
Abstract: We report a delicate design and controllable preparation of Li4 Ti5 O12 /TiO2 /Carbon (LTO-T/C) spherical heterostructure and its application as anode for Lithium Ion Batteries (LIBs). The as-prepared self-assembled LTO-T/C spheres exhibit a chrysanthemum-like structure with abundant nanowires on the surface, which provide a large specific surface area and many transmission channels for electrons and ions transport. The carbon layer around the sphere could further increase the conductivity of the sample. As expected, the tailored LTO-T/C electrode shows excellent rate performance and outstanding reversible capacity of 220 mAh g −1 and 125 mAh g −1 after 500 cycles at the current density of 1.0 A g −1 and 10 A g −1, respectively. The improved cyclic and rate performance are attributed to its unique heterostructure and self-assembled microsphere morphology.